Interpretability of Faith and Its Role in Practical Theology Orientations - Seyyedeh Shima Anoosheh; Ahmad Karimi (پژوهشنامه فلسفه دین, 2022)
"Faith", as one of the most important companions in human history, is a factor in creating homogeneous religious communities, but at the same time, with the emergence of interpretive disagreements, it becomes a cause of conflict among individuals. Even some of the greatest battles in history are the result of people rejecting their counterpart religious interpretations. By introducing an understanding of faith that considers it to be interpretable and states that different social, cultural, and even natural and historical circumstances and situations influence individual perceptions of faith, we can help increase tolerance and flexibility in society. The religious teachings of Islam, despite differences in individuals' capacities for accepting and expressing faith, have always encouraged brotherhood and forbade individuals from imposing heavier burdens on those with less capacity. By using Scriptural evidence, this article attempts to prove that faith is interpretable. Consequently, the article clarifies that, on the one hand, due to the "gradation of faith", there are multiple interpretations of it in society and, on the other hand, achieving the important principle of brotherhood will depend on understanding this aspect of faith and promoting individuals' flexibility and tolerance. It will allow individuals to live peacefully and empathically, free from violence.